Insights from a pharmacometric analysis of HDMTX in adults with cancer: Clinically relevant covariates for application in precision dosing. Issue 2 (11th September 2022) - Ibarra, Manuel; Combs, Ryan; Taylor, Zachary L.; Ramsey, Laura B.; Mikkelsen, Torben; Buddington, Randal K.; Heldrup, Jesper; Barreto, Jason N.; Guscott, Martin; Lowe, Jennifer; Hurmiz, Charles; Marada, Suresh; et al.
Abstract : Aims: High‐dose methotrexate (HDMTX) is an essential part of the treatment of several adult and paediatric malignancies. Despite meticulous supportive care during HDMTX administration, severe toxicities, including acute kidney injury (AKI), may occur contributing to patient morbidity. Population pharmacokinetics provide a powerful tool to predict time to clear HDMTX and adjust subsequent doses. We sought to develop and validate pharmacokinetic models for HDMTX in adults with diverse malignancies and to relate systemic exposure with the occurrence of severe toxicity. Methods: Anonymized, de‐identified data were provided from 101 US oncology practices that participate in the Guardian Research Network, a non‐profit clinical research consortium. Modelled variables included clinical, laboratory, demographic and pharmacological data. Population pharmacokinetic analysis was performed by means of nonlinear mixed effects modelling using MonolixSuite. Results: A total of 693 HDMTX courses from 243 adults were analysed, of which 62 courses (8.8%) were associated with stage 2/3 acute kidney injury (43 stage 2, 19 stage 3). A three‐compartment model adequately fitted the data. Time‐dependent serum creatinine, baseline serum albumin and allometrically scaled bodyweight were clinically significant covariates related to methotrexate clearance. External evaluation confirmed a satisfactory predictive performance of the model in adults receiving HDMTX. Dose‐normalized methotrexate concentration at 24 and 48 hours correlated with AKI incidence. Conclusion: We developed a population pharmacometric model that considers weight, albumin and time‐dependent creatinine that can be used to guide supportive care in adult patients with delayed HDMTX elimination.